2014
DOI: 10.1017/s0954579414000248
|View full text |Cite
|
Sign up to set email alerts
|

A gender-balanced approach to the study of peer victimization and aggression subtypes in early childhood

Abstract: A short-term longitudinal study during early childhood (N = 301; 155 girls; M = 44.76 months old, SD = 8.20) investigated the prospective associations between peer victimization and aggression subtypes. Specifically, observations of relational and physical victimization as well as teacher reports of the forms (i.e., relational and physical) and functions (i.e., proactive and reactive) of aggression were collected at two time points during an academic year. Within- and between-group gender differences were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 69 publications
3
31
1
2
Order By: Relevance
“…The results of the study conform to the classical study by Björkqvist, Lagerspetz, and Kaukiainen (1992) and Archer (2004) and point to the importance of scripts for social codes of behaviour applicable to girls and boys, which are entrenched in the social knowledge of a given culture. The finding is consistent with the model proposed by Ostrov and Godleski (2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the study conform to the classical study by Björkqvist, Lagerspetz, and Kaukiainen (1992) and Archer (2004) and point to the importance of scripts for social codes of behaviour applicable to girls and boys, which are entrenched in the social knowledge of a given culture. The finding is consistent with the model proposed by Ostrov and Godleski (2014).…”
Section: Discussionsupporting
confidence: 93%
“…Their studies show that girls more commonly engage in gender-consistent aggressive behaviours. Accordingly, girls usually opt for relational rather than physical aggression (Ostrov, 2014;Card et al, 2008;Murray-Close et al, 2016;Putallaz et al, 2007).…”
Section: Models For Studying Conditions Underlying the Development Ofmentioning
confidence: 99%
“…Relational victimization is defined as the receipt of relational aggression, which is the removal or threat of the removal of relationships (e.g., social exclusion, spreading malicious secrets or lies, friendship withdrawal threats). We continue to echo previous calls for the use of the term ''physical'' rather than ''overt'' victimization (Godleski, Kamper, Ostrov, Hart, & Blakely-McClure, 2014). Overt victimization was initially used by Grotpeter (1995, 1996) to denote a composite of physical and verbal aggression=victimization.…”
Section: Definitionsmentioning
confidence: 57%
“…Subsequent research extended this work to the study of early childhood (e.g., Bonica, Arnold, Fisher, Zeljo, & Yershova, 2003;Crick, Casas, & Ku, 1999), adolescents (Schafer, Werner, & Crick, 2002), and emerging adults (Linder, Crick, & Collins, 2002). The early work also demonstrated that girls were more likely to experience relational victimization than they were to receive physical victimization (Crick & Bigbee, 1998;Roecker Phelps, 2001), which has been replicated with relational aggression studies as well (e.g., Ostrov, Kamper, Hart, Godleski, & Blakely-McClure, 2014;Putallaz et al, 2007). This early theoretical and empirical work has been generative with a recent PsycINFO search using the keyword ''relational victimization'' yielding 259 peerreviewed publications.…”
mentioning
confidence: 79%
“…Approximately 46% of teachers had a bachelor’s degree and 19% had a master’s degree. This dataset was used in a prior manuscript, but there was no overlap in the measures or research questions previously addressed (see Ostrov, Kamper, Hart, Godleski, & Blakely-McClure, 2014). …”
Section: Methodsmentioning
confidence: 99%